ANALISIS DETERMINAN KEJADIAN COVID-19 DI KOTA BATAM TAHUN 2020 - Shafira Wina Adide (2021)
COVID-19 is a disease caused by a new virus, named SARS-CoV-2 which was first discovered in Wuhan, China, in December 2019. Since it was first discovered until September 2, 2020, COVID-19 has spread to 213 countries around the world with total cases reaching more than 25 million population and more than 800 thousand deaths. This study aimed to analyze the determinants of the incidence of COVID-19 in Batam City. This research used a cross-sectional design study. The number of samples was 360 people who were taken using simple random sampling technique from the surveillance of COVID-19 data Batam Health Office. This study used Chi-Square and multiple logistic regression. The variables in this study were divided into three, sociodemography (age, gender, education, knowledge, occupation, and income), comorbid (obesity, diabetes, hypertension, and cardiovascular), and health protocols (keep your distance, wear a mask, and wash your hands). The results of the bivariate analysis showed that social distancing and wearing masks had a significant relationship with the incidence of COVID-19. The results of the multivariate analysis showed that social distancing was the most influential factor in the incidence of COVID-19 with POR = 2.5 (95% CI = 1.6-4.0). We can conclude that people whose not comply with social distancing has a greater risk to face COVID-19. It is recommended for the community to comply with health protocol, particularly social distancing, to prevent the spread of COVID-19